The impact of urban gardening on household food security: evidence from Makhanda East, Eastern Cape Province, South Africa - Bruwer, Guillaume Marcel Xavier (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
Urban gardening in townships is a common coping strategy employed by poor inhabitants to improve food security, earn income through sales, and generate cost-savings through home consumption of fresh produce. Food security is a cornerstone of human development and welfare, and the achievement thereof remains a global challenge. The majority of academic research and policy documentation traditionally positions food insecurity as a rural phenomenon. However, recent trends point to an increase in food insecurity in urban areas, particularly in low-income areas such as townships. In South Africa, rapid urbanization has led to burgeoning townships and rapidly expanding low-income informal settlements characterised by poverty, unemployment, and food insecurity. Research concerned with the role that urban agricultural production plays in contributing to the food security of poor households is scarce and not well understood. This research, therefore, aimed to contribute to the limited research which specifically examines urban food security, and the role urban agriculture play in the achievement of household food security. The study employed collective action theory and utility theory to firstly provides an in-depth examination of the determinants of participation in urban gardening using Probit regression modeling. The second research objective was to perform an impact evaluation of participation in urban gardening on selected household food security indicators including Household Dietary Diversity Scores (HDDS), the Household Hunger Scale (HHS) and the Coping Strategy Index (CSI) using Propensity Score Matching (PSM). Purposive and snowball sampling methods were employed to obtain a sample of 60 urban gardeners and a control group of 55 non-gardening households from Extension 6, 7 and 10 townships as well as Joza Location in Makhanda East, Eastern Cape Province. Households were surveyed using a structured household food security questionnaire. A focus group discussion was held with the Linomtha Community Garden members and key informant interviews were undertaken with important stakeholders such as the local extension officers. Descriptive analysis revealed that urban gardening households (UGs) had older household heads who were less educated, and that land and water availability were the dominant constraints to increases in agricultural production. Results from the probit and average marginal effects models showed that the likelihood of participation significantly increased when household unemployment and dependency increased and that households who were engaged in off-farm economic activity were more likely to participate in urban gardening. The impact evaluation was performed using PSM and Average Treatment Effect on the Treated (ATT). Analysis illustrated that participation in urban gardening does significantly reduce both the full CSI and Reduced CSI. Thus, participation in urban gardening improves the food security of participating households by significantly reducing the frequency of participating households (UGs) applying undesirable coping strategies such as sending children elsewhere other than the household, borrowing food from other households and reducing the number of meals eaten in a day due to food shortages. This study posits that urban gardening alone will not eradicate the rampant food insecurity and poverty which pervades in South Africa's townships. However, urban gardening participation does contribute to the construction of a sustainable, urban livelihood by reducing the number and severity of the undesirable coping strategies that food insecure households employ by providing some nutritious produce as well improved social capital through gardening networks and supporting institutions. It is recommended that policy makers, at a national and municipal level, need to create a clearer directive for the integration of urban food production into the urban food marketplace thus increasing access to income generating channels for small-scale home, and community gardeners. Co-operation between private and public institutions for food security and urban gardeners needs to be fostered and awareness of opportunities to participate in urban gardens needs to be improved. Central to the developmental challenges that rapid increases in urbanization and food insecurity in poor urban areas, is the need for national and local governments to improve access to economic opportunities in township areas - both in urban agriculture and in other, skills intensive sectors.
Keywords: Food security -- South Africa -- Makhanda; Urban agriculture -- South Africa -- Makhanda; Urban gardening -- South Africa -- Makhanda; Sustainable development -- South Africa -- Makhanda; South Africa Economic conditions; Subsistence farming -- South Africa -- Makhanda; Economic impact analysis -- South Africa -- Makhanda; Propensity Score Matching (PSM)